Comprehensive Evaluation of Urban Economic Development in Yangtze River Delta Based on Cluster-Principal Component Analysis - Quan Xie; Xin-Yue Dong; Ke Yu; Ling-Yu Zhang; Yun-Hua Xu (Complexity)
The study of the Yangtze River Delta urban agglomeration provides a reference for regional construction. We set up a suitable cluster model and a comprehensive evaluation model to evaluate the urban economic development and provide the basis for the government to formulate and adjust the economic measures. We use the heat map of correlation coefficient to eliminate the economic indicators that are less correlated with per capita GDP and use grey correlation analysis to detect the degree of correlation of economic indicators. The optimal method is determined by comparing the results of K-means clustering and fuzzy C-means clustering. In addition, we use principal component analysis to rank the status of urban economic development. The results show that the relationship between the added value of primary industry, the added value of agriculture, forestry, animal husbandry and fishery, and per capita GDP is close to 0. Regional development level is not balanced. Chizhou, Xuancheng, Bengbu, and other cities lag behind in the economic rankings. Finally, it is suggested to reform the laggard cities and try to improve their economic strength from various economic indicators.